School readiness, grade one academic achievement, and adaptive competency as functions of the length of kindergarten training - Vergara, Ma. Belen L. (Animo Repository, 1991)
This study sought to determine the relationship of length of kindergarten training, school readiness, grade one academic achievement, and adaptive competency. It was hypothesized that there is a significant difference in the school readiness of grade one pupils who had two years of kindergarten training, one year of kindergarten training, or no kindergarten training. Secondly, there is a significant difference in the grade one academic achievement of the three groups of subjects. Thirdly, there is a significant difference in the adaptive competency of the three groups of grade one pupils. Lastly, there is a significant relationship between school readiness and grade one academic achievement, school readiness and adaptive competency, and grade one academic achievement and adaptive competency. Subjects were 120 randomly selected grade one pupils of St. Mary's Academy grouped according to length of kindergarten training (two-year, one-year, or none). Each of the three groups was composed of 40 grade one pupils (20 males, 20 females). The Metropolitan Readiness Tests were administered to measure pupil's school readiness. The grade-point average of the first two quarters of grade one yielded pupil's grade one academic achievement. The sum of parent's and teacher's adaptive competency ratings of each child assessed each pupil's adaptive competency. One-way Analysis of Variance and Pearson Product-Moment Correlation were employed in the analysis of the data. The findings of the study showed that there is a significant difference in the performance of pupils who had two-year, one-year, or no kindergarten training on school readiness, F(2,117)=293.57, p.05, grade one academic achievement, F(2,117) adaptive competency, F(2,117)=168.15, p.05. There is a significant relationship between school readiness and grade one academic achievement (rOn the basis of these findings, it was concluded that grade one pupils who had two years of kindergarten are more prepared for grade one work, have higher academic achievement, and possess better adaptive competency. It was further concluded that school readiness and adaptive competency influence pupils' performance in the first grade.Further studies are recommended to determine long-term effects of attendance in the preschool on students' academic performance in higher grade levels.